Efficient Visible–Near‐Infrared Hybrid Perovskite:PbS Quantum Dot Photodetectors Fabricated Using an Antisolvent Additive Solution Process. Issue 23 (8th October 2018) - Zhao, Dan; Huang, Jiang; Qin, Ruiheng; Yang, Genjie; Yu, Junsheng
Abstract: Organometal lead‐halide perovskites demonstrate excellent photovoltaic performance in the visible (Vis) region. However, their lack of response in the near‐infrared (NIR) region limits their applications in broadband photodetectors. Herein, an efficient Vis–NIR perovskite photodetector (PePD) created by doping PbS quantum dots (QDs) in perovskite precursors via an antisolvent additive solution process is reported. By changing the volume of the antisolvent additive, perovskite hybrid films of MAPbI3 :PbS QDs with good crystallinity and uniform grain size are created. The resultant Vis–NIR PePD exhibits a specific detectivity of 10 12 and 10 11 Jones in the visible and NIR regions, respectively. These results suggest that the antisolvent additive solution process can disperse PbS QDs between perovskite grain boundaries and control the perovskite crystallinity and morphology, providing a simple method to broaden the spectral response range of PePDs. Abstract : By verifying the volume of antisolvent additive in the precursor, the perovskite film of MAPbI3 :PbS quantum dots with good crystallinity and uniform grain size has been achieved, exhibiting a broad spectral response ranged from visible to near‐infrared.